Tin-based perovskite light-absorbing layer, tin-based perovskite solar cell and preparation method thereof
By introducing spirobisfluorene molecules into the light-absorbing layer of tin-based perovskite solar cells, the problems of low fill factor, insufficient efficiency, and poor stability of tin-based perovskite solar cells were solved. This achieved synergistic optimization of bulk and interfacial carrier dynamics, improving cell performance and stability.
Patent Information
- Application Number
- CN202611232130.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-11-03
AI Technical Summary
Existing tin-based perovskite solar cells suffer from problems such as low fill factor, insufficient photoelectric conversion efficiency, poor stability, unsatisfactory bulk carrier dynamics, low interfacial carrier extraction efficiency, and severe nonradiative recombination. Existing improvement schemes cannot achieve synergistic optimization of bulk and interfacial carrier dynamics.
Spirobifluorene molecules (such as 2,2',7,7'-tetratetra[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene) are introduced into the light-absorbing layer of tin-based perovskite. Through strong coordination, they bind with tin-based perovskite, regulate crystallization kinetics, inhibit Sn2+ oxidation, enhance interfacial interactions, act as molecular binders to connect grains, and optimize bulk and interfacial properties.
It significantly improved the fill factor, photoelectric conversion efficiency and long-term stability of tin-based perovskite solar cells. The fill factor reached 81.8%, the photoelectric conversion efficiency reached 17.74%, and the stability was 89% of the initial efficiency after 1100h storage under environmental conditions and 86% after 1000h of continuous 1-sun illumination.
Smart Images

Figure CN123035808A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite solar cell technology, and in particular to a tin-based perovskite light-absorbing layer, a tin-based perovskite solar cell, and a method for preparing the same. Background Technology
[0002] Currently, tin-based perovskite solar cells (TPSCs), as an environmentally friendly photovoltaic technology, have become an important candidate for next-generation photovoltaic technology due to their advantages such as low toxicity, high carrier mobility, and high theoretical power conversion efficiency (PCE). Their PCE has increased from the initial 0.9% to 17.89%. However, as the demand for efficient and stable devices in photovoltaic technology continues to rise, existing tin-based perovskite solar cells are gradually revealing many shortcomings, specifically: 1. Existing tin-based perovskite solar cells generally have low fill factors (typically <78%), making it difficult to overcome the bottleneck in photoelectric conversion efficiency. The core reason lies in the unsatisfactory bulk carrier dynamics, Sn² + The inherent strong Lewis acidity of the precursor leads to uncontrolled crystallization kinetics, resulting in perovskite films with numerous defects, low coverage, and poor crystallinity. This, in turn, triggers severe nonradiative recombination, shortens carrier lifetime, and inhibits device performance. For example, the defect density of unoptimized tin-based perovskite films can reach as high as 1.78 × 10⁻⁶. 15 cm -3 This results in the device's photoelectric conversion efficiency reaching only about 14%, which cannot meet the requirements for high-performance photovoltaic devices.
[0003] 2. Existing tin-based perovskite solar cells exhibit low interfacial carrier extraction efficiency, weak interfacial coupling between the perovskite layer and adjacent charge transport layers, and numerous defects at the top and buried interfaces. These defects not only hinder carrier extraction but also exacerbate nonradiative recombination at the interface. Furthermore, Sn... 2+ Sn is easily formed at the interface. 4+ The defects further deteriorate the device performance; in addition, the long-term stability of the device is poor. After 1100 hours of storage under environmental conditions, the packaged device without interface and bulk optimization can only retain 70% of the initial efficiency, and after 1000 hours of continuous 1-sun illumination, it can only retain 62% of the initial efficiency.
[0004] 3. Currently, most molecular engineering improvement solutions for the above problems in the industry can only optimize a single aspect of carrier dynamics, either improving bulk carrier transport or increasing carrier extraction efficiency at a single interface. They cannot achieve synergistic optimization of the bulk phase and the top and buried interfaces, resulting in limited improvement effects and failing to fundamentally solve the problems of low fill factor, insufficient efficiency, and poor stability.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] One of the objectives of this invention is to provide a tin-based perovskite light-absorbing layer to at least solve one of the technical problems existing in the prior art.
[0007] The second objective of this invention is to provide a method for preparing a tin-based perovskite light-absorbing layer.
[0008] The third objective of this invention is to provide a tin-based perovskite solar cell.
[0009] The fourth objective of this invention is to provide a method for preparing a tin-based perovskite solar cell.
[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a tin-based perovskite light-absorbing layer, comprising: a tin-based perovskite crystal phase, and spirobisfluorene molecules doped in the tin-based perovskite crystal phase; The spirobifluorene molecules include 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene.
[0011] Furthermore, the spirobisfluorene molecules are doped at the surface and grain boundaries of the tin-based perovskite crystal phase.
[0012] Secondly, the present invention provides a method for preparing a tin-based perovskite light-absorbing layer, comprising the following steps: A tin-based perovskite precursor solution containing spirobisfluorene molecules is applied to the hole transport layer, followed by annealing to obtain the tin-based perovskite light-absorbing layer.
[0013] Furthermore, the mass concentration of the spirobisfluorene molecule in the tin-based perovskite precursor solution is 0.5~3 mg / mL; Preferably, the concentration of the tin-based perovskite precursor solution is 0.9~1.4 M; Preferably, the components of the tin-based perovskite precursor solution include a tin source, an organic cation source, and additives; Preferably, the tin source includes one or both of stannous iodide and stannous fluoride; the organic cation source includes one or more of formamidinium hydrobromide, phenylethyl ammonium bromide, and methylamine hydrobromide; and the additive includes the spirobisfluorene molecule. Preferably, the molar ratio of the phenylethyl ammonium bromide, the formamidinium hydrobromide, the methylamine hydrobromide, the stannous iodide, and the stannous fluoride is 0.10~0.20:0.70~0.80:0.05~0.15:1:0.05~0.1; Preferably, the tin-based perovskite precursor solution further comprises a solvent; the solvent comprises one or both of dimethyl sulfoxide and N,N-dimethylformamide. Preferably, the volume ratio of the dimethyl sulfoxide to the N,N-dimethylformamide is 1:4~9.
[0014] Furthermore, the application method includes spin coating; Preferably, the spin coating rotation speed is 4000~8000 rpm, the acceleration is 500~2500 rpm / s, and the spin coating time is 30~60 s; Preferably, the antisolvent is added dropwise during the 10-20 s spin coating process; the antisolvent includes one or more of chlorobenzene, toluene, ethyl acetate, and isopropanol; the amount of antisolvent added is 250-400 μL. The annealing temperature is 70~90℃, and the annealing time is 8~15 min; Preferably, the annealing treatment is carried out in an inert atmosphere with an oxygen content of less than 0.1 ppm.
[0015] Thirdly, the present invention provides a tin-based perovskite solar cell, comprising a transparent conductive substrate, a hole transport layer, the tin-based perovskite light-absorbing layer or the tin-based perovskite light-absorbing layer prepared by the preparation method, an electron transport layer, a hole blocking layer, and a metal electrode stacked sequentially from bottom to top.
[0016] Furthermore, the transparent conductive substrate includes one or more of the following: indium tin oxide conductive glass, indium-free metal oxide transparent conductive oxide film, metal-based transparent conductive network, carbon-based transparent electrode, and conductive polymer film; Preferably, the hole transport layer includes a PEDOT:PSS hole transport layer; Preferably, the electron transport layer comprises an indene-C60 bisadduct layer; Preferably, the hole-blocking layer comprises a 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline layer; Preferably, the metal electrode is a silver electrode with a thickness of 80~100 nm.
[0017] Fourthly, the present invention provides a method for preparing a tin-based perovskite solar cell, comprising the following steps: sequentially stacking a hole transport layer, a tin-based perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode on a transparent conductive substrate.
[0018] Furthermore, the hole transport layer is prepared by spin-coating a hole transport layer precursor solution onto the transparent conductive substrate and then annealing it. Preferably, the hole transport layer precursor solution is a PEDOT:PSS aqueous dispersion; the spin coating speed is 4000~6000 rpm, the spin coating time is 30~40 s; the annealing temperature is 120~140℃, and the annealing time is 15~20 min.
[0019] Furthermore, the electron transport layer is prepared by spin-coating an electron transport layer precursor solution onto the surface of the tin-based perovskite light-absorbing layer and then annealing it; the electron transport layer precursor solution includes an indene-C60 bis-adduct; the spin-coating speed is 2000 rpm and the spin-coating time is 30 s; the annealing temperature is 70℃ and the time is 10 min. Preferably, the hole blocking layer is prepared by spin-coating a hole blocking layer precursor solution onto the surface of the electron transport layer and then annealing it; the hole blocking layer precursor solution contains 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline; the spin-coating speed is 6000 rpm and the spin-coating time is 30 s; the annealing temperature is 70℃ and the time is 10 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The tin-based perovskite light-absorbing layer provided by this invention involves introducing 2,2,7,7-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorene (SBF, i.e., Spiro-OMeTAD) molecules into the tin-based perovskite light-absorbing layer. The triphenylamine group in the Spiro-OMeTAD molecule can effectively suppress Sn by forming a coordination interaction with Sn in the tin-based perovskite. 2+ Furthermore, its rigid helical framework can block water and oxygen intrusion and inhibit ion migration, thereby significantly improving the long-term stability of the tin-based perovskite solar cell. It can also alleviate residual lattice stress, regulate perovskite crystallization kinetics, slow down the crystallization rate, improve the crystal quality of the perovskite film, reduce defect density, and achieve synergistic optimization of bulk and interfacial carrier dynamics, thereby significantly improving the fill factor, photoelectric conversion efficiency and long-term stability of the tin-based perovskite solar cell. Attached Figure Description
[0021] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0022] Figure 1A schematic diagram of SBF doping in tin-based perovskite thin films and the corresponding TPSC device structure; Figure 2 Steady-state photoconductivity spectroscopy (PL spectra) was used to characterize the tin-based perovskite films of Comparative Example 1 (untreated) and Example 1 (SBF treated), the stacked structures of tin-based perovskite and PEDOT:PSS hole transport layers (HTLs) of Comparative Example 1 and Example 1, and the stacked structures of tin-based perovskite and ICBA electron transport layers (ETLs) of Comparative Example 1 and Example 1. Figure 3 In the middle (a), the electronic surface potential diagram shows that the electronic surface potential of the SBF molecule reveals that the methoxy group exhibits a region of strong electron enrichment. Figure 3 In the middle (b), the density functional theory (DFT) calculation plot shows that the binding energy between SBF molecules and SnI2 is -0.95 eV, which confirms that there is a strong interaction between them. Figure 4 The images show the average particle size distribution of tin-based perovskite films in Comparative Example 1 (ab) and Example 1 (cd), and cross-sectional scanning electron microscope images of Comparative Example 1 (e) and Example 1 (f). Figure 5 XRD patterns of tin-based perovskite films of Comparative Example 1 and Example 1 (a), FWHM of (100) crystal plane images of TPSCs of Comparative Example 1 and Example 1 (b), PL mapping of tin-based perovskite films of Comparative Example 1 (c) and Example 1 (d), SCLC curves of tin-based perovskite films of Comparative Example 1 and Example 1 (e), and TRPL curves of tin-based perovskite films of Comparative Example 1 and Example 1 (f). Figure 6 For TPV and TPC characterization, (a) TPV measurement of tin-based perovskite films of Comparative Example 1 (untreated) and Example 1 (SBF treated), and (b) TPC measurement of tin-based perovskite films of Comparative Example 1 (untreated) and Example 1 (SBF treated). Figure 7 XPS spectra of the Sn 3d region on the top surface of the perovskite of Comparative Example 1 (untreated) (a) and Example 1 (SBF treated) (b); Sn 3d region on the top interface of the tin-based perovskite films of Comparative Example 1 and Example 1. 2+ With Sn 4+ Percentage (c); XPS spectra of the Sn 3d region of the buried surface of the perovskite in Comparative Example 1 (d) and XPS spectra of the Sn 3d region of the buried surface of the perovskite in Example 1 (treated with SBF) (e); Sn at the buried interface of the tin-based perovskite films of Comparative Example 1 and Example 1 2+ With Sn 4+ Percentage (f); Figure 8 For TPSCs (a) with an ITO / PEDOT:PSS / perovskite / ICBA / BCP / Ag structure, Comparative Example 1 and Example 1 have small areas (0.04 cm²). 2 )TPSCs JV Forward and reverse curves of TPSCs in curves (b), Comparative Example 1 (c), and Example 1 (d) JV curve; Figure 9 TPSCs at different SBF concentrations of 0.2, 0.5, 1.0, 1.5, and 2.0 mg / mL JV curve; Figure 10 Photovoltaic parameter statistics for TPSCs in Comparative Example 1 (untreated) and Example 1 (SBF treated): PCE(a), V oc (b), J sc (c) and FF(d); Figure 11 For an area of 1 cm 2 TPSCs (unprocessed) and TPSCs (SBF processed) JV Curve (a); Long-term stability of packaged Comparative Example 1 (untreated) and Example 1 (SBF treated) TPSCs under shelf storage and continuous 1-day equivalent white LED irradiation (b). Figure 12 The diagram shows the time efficiency of TPSCs in Example 1. Detailed Implementation
[0023] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] The first aspect of the present invention provides a tin-based perovskite light-absorbing layer, comprising: a tin-based perovskite crystal phase, and spirobisfluorene molecules doped in the tin-based perovskite crystal phase; the spirobisfluorene molecules include 2,2',7,7'-tetratetra[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobisfluorene.
[0026] This invention introduces 2,2',7,7'-tetratetra[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (SBF) molecules into a tin-based perovskite precursor solution. SBF molecules form a strong coordination relationship with the tin-based perovskite precursor, thereby regulating the crystallization kinetics of the perovskite. Simultaneously, SBF molecules act as a molecular binder, achieving connections between perovskite grains and effectively passivating perovskite grain boundaries. Furthermore, it strengthens the interaction between the top of the perovskite layer and the buried interface, ultimately achieving synergistic optimization of bulk and interfacial carrier dynamics. This invention can simultaneously optimize the bulk crystallization quality and interfacial properties of tin-based perovskites, synergistically improving bulk and interfacial carrier dynamics, thereby enhancing the fill factor, photoelectric conversion efficiency, and long-term stability.
[0027] In some preferred embodiments, the spirobisfluorene molecules are doped at the surface and grain boundaries of the tin-based perovskite crystal phase. For example... Figure 1 As shown, SBF molecules simultaneously regulate the bulk crystallinity of the perovskite layer and its top and buried interfaces.
[0028] The second aspect of the present invention provides a method for preparing a tin-based perovskite light-absorbing layer, comprising the following steps: applying a tin-based perovskite precursor solution containing spirobisfluorene molecules onto a hole transport layer, followed by annealing, to obtain the tin-based perovskite light-absorbing layer.
[0029] Specifically, the method for preparing the tin-based perovskite light-absorbing layer includes: In an inert atmosphere, a tin-based perovskite precursor solution doped with SBF (Spiro-OMeTAD) is spin-coated onto the surface of the hole transport layer. During the spin-coating process, an antisolvent is added to assist crystallization. After annealing, a dense, pinhole-free, and highly crystalline tin-based perovskite light-absorbing layer is formed. SBF molecules are uniformly distributed in the perovskite bulk phase, top, and buried interface, and are enriched at the buried interface, achieving synergistic optimization of bulk phase and interface properties.
[0030] The concentration of the tin-based perovskite precursor solution is 0.9~1.4 M, for example, it can be 0.9 M, 1 M, 1.1 M, 1.2 M, 1.3 M, 1.4 M, etc., preferably 1.2 M.
[0031] Preferably, the components of the tin-based perovskite precursor solution include a tin source, an organic cation source, and additives; the tin source includes one or both of stannous iodide and stannous fluoride; the organic cation source includes one or more of formamidinium hydrobromide, phenylethyl ammonium bromide, and methylamine hydrobromide; and the additives include the spirobisfluorene molecules.
[0032] The molar ratio of phenylethyl ammonium bromide, formamidinium hydrobromide, methylamine hydrobromide, stannous iodide, and stannous fluoride is 0.10~0.20:0.70~0.80:0.05~0.15:1:0.05~0.1; where "0.10~0.20" can be, for example, 0.10, 0.50, 0.15, 0.20, etc.; "0.70~0.80" can be, for example, 0.70, 0.75, 0.80, etc.; "0.05~0.15" can be, for example, 0.05, 0.10, 0.15, etc.; and "0.05~0.1" can be, for example, 0.05, 0.075, 0.1, etc. A preferred molar ratio is 0.15:0.75:0.10:1:0.10.
[0033] More preferably, the tin-based perovskite precursor solution is prepared by dissolving phenylethyl ammonium bromide, formamidinium hydrobromide, methylamine hydrobromide, stannous iodide and stannous fluoride in a mixed solvent of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), while simultaneously doping with SBF (Spiro-OMeTAD).
[0034] In some preferred embodiments, the spirobisfluorene molecule is present in a concentration of 0.5–3 mg / mL in the tin-based perovskite precursor solution, for example, 0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, etc. The preferred concentration of SBF (Spiro-OMeTAD) is 1 mg / mL (this concentration achieves the best synergistic effect of crystallization control and carrier kinetic optimization, increasing the average grain size of the perovskite film from 350 nm to 500 nm and the defect density from 1.78 × 10⁻⁶). 15 cm -3 Reduced to 0.99×10 15 cm -3 ).
[0035] Preferably, the volume ratio of dimethyl sulfoxide to N,N-dimethylformamide in the mixed solvent is 1:(4~9), for example, it can be 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc., preferably 1:4, which can effectively improve the solubility of the precursor and the film formation quality, and help the SBF molecules to be uniformly dispersed.
[0036] In some preferred embodiments, the application method includes spin coating, and more preferably a one-step spin coating process.
[0037] Preferably, the spin coating speed is 4000~8000 rpm, for example, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, etc., and more preferably 6000 rpm; the acceleration is 500~2500 rpm / s, for example, 500 rpm / s, 1000 rpm / s, 1500 rpm / s, 2000 rpm / s, 2500 rpm / s, etc., and more preferably 2000 rpm / s; the spin coating time is 30~60 s, for example, 30 s, 40 s, 50 s, 60 s, etc., and more preferably 50 s.
[0038] Preferably, the antisolvent is added dropwise at the 10th to 20th second of spin coating, for example, at 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s, 20 s, etc., and more preferably at 15 s; the antisolvent includes one or more of chlorobenzene, toluene, ethyl acetate and isopropanol; the amount of antisolvent added is 250 to 400 μL, for example, at 200 μL, 250 μL, 300 μL, 400 μL, etc., and more preferably at 340 μL, which can effectively control the perovskite crystallization rate and, together with SBF molecules, further reduce pinholes and defects in the film.
[0039] Preferably, the annealing temperature is 70~90℃, for example, 70℃, 80℃, 90℃, etc., more preferably 80℃, and the annealing time is 8~15 min, for example, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc., more preferably 10 min, which can promote perovskite grain growth, improve crystallinity, and inhibit Sn. 2+ Oxidation.
[0040] Preferably, the annealing treatment is carried out in an inert atmosphere with an oxygen content of less than 0.1 ppm. The inert atmosphere is nitrogen or argon, preferably nitrogen, which can effectively suppress Sn²⁺ during the annealing process. + Oxidation ensures that SBF molecules react with Sn. 2+ Its coordination function is stable and effective.
[0041] A third aspect of the present invention provides a tin-based perovskite solar cell, comprising a transparent conductive substrate, a hole transport layer, a tin-based perovskite light-absorbing layer or a tin-based perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode stacked sequentially from bottom to top.
[0042] The ITO conductive layer has a thickness of 90-120 nm, the hole transport layer has a thickness of 20-40 nm, the tin-based perovskite light-absorbing layer has a thickness of 350-500 nm, the ICBA electron transport layer has a thickness of 15-30 nm, the BCP hole blocking layer has a thickness of 6-10 nm, and the metal electrode has a thickness of 80-100 nm.
[0043] The tin-based perovskite solar cell provided by this invention is a type of tin-based perovskite solar cell based on the synergistic regulation of bulk phase and interfacial carrier dynamics by spirobisfluorene molecules. It is particularly suitable for the fabrication and optimization of high-efficiency, stable, and environmentally friendly lead-free perovskite photovoltaic devices. This invention achieves synergistic optimization of bulk phase and interfacial carrier dynamics through single doping with SBF molecules, overcoming the limitation of existing molecular engineering methods that can only optimize a single aspect: SBF molecules can simultaneously regulate the perovskite bulk phase crystallinity (delaying crystallization, increasing grain size, and reducing defect density) and interfacial properties (inhibiting Sn). 2+ Oxidation, optimization of interfacial potential, and relief of residual stress (these processes promote bulk carrier transport and suppress bulk nonradiative recombination, while also accelerating interfacial carrier extraction and reducing interfacial nonradiative recombination, thus achieving a comprehensive improvement in the carrier dynamics of the entire device) are key benefits. Specifically, SBF molecules interact with Sn... 2+ The strong coordination effect inhibits its oxidation and reduces Sn 4+ Defect generation; its rigid helical framework can block water and oxygen intrusion, alleviate residual stress in the lattice, and regulate perovskite crystallization dynamics, thereby improving crystal quality and reducing defect density; in addition, SBF molecules can act as molecular binders to connect adjacent perovskite grains and passivate grain boundaries, while strengthening the interfacial interaction between the perovskite layer and the hole transport layer and electron transport layer, optimizing the interfacial potential, accelerating carrier extraction, and synergistically improving the bulk and interfacial carrier dynamics, significantly improving the fill factor, photoelectric conversion efficiency and long-term stability of the battery.
[0044] This battery features a highly crystalline perovskite light-absorbing layer, optimized bulk and interface properties, and uniformly distributed SBF molecules in the perovskite bulk phase, top, and buried interface. This enables synergistic optimization of bulk and interface carrier dynamics, resulting in excellent photoelectric performance.
[0045] This invention solves the technical problems of existing tin-based perovskite solar cells (TPSCs), such as low fill factor (FF) (typically below 78%), insufficient photoelectric conversion efficiency, poor stability, unsatisfactory bulk carrier dynamics, low interfacial carrier extraction efficiency, and severe nonradiative recombination. The fabrication process of this invention is simple and highly practical, and can be widely applied in the field of photovoltaic devices. Tin-based perovskite solar cells prepared using this invention show significantly improved fill factor and photoelectric conversion efficiency, and greatly enhanced stability.
[0046] In some preferred embodiments, the transparent conductive substrate includes one or more of indium tin oxide (ITO) conductive glass, indium-free metal oxide transparent conductive oxide (TCO) thin films, metal-based transparent conductive networks, carbon-based transparent electrodes, and conductive polymer thin films.
[0047] Preferably, the hole transport layer includes a PEDOT:PSS hole transport layer; Preferably, the electron transport layer comprises an indene-C60 bisadduct layer; Preferably, the hole-blocking layer comprises a 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline layer; Preferably, the metal electrode is a silver electrode with a thickness of 80~100 nm, such as 80 nm, 90 nm, 100 nm, etc., and more preferably 90 nm. It has good conductivity and stability and can effectively collect charge carriers.
[0048] In this invention, the overall structure of the device is ITO / PEDOT:PSS / tin-based perovskite / ICBA / BCP / Ag.
[0049] The fourth aspect of the present invention provides a method for preparing a tin-based perovskite solar cell, comprising the following steps: sequentially stacking a hole transport layer, a tin-based perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode on a transparent conductive substrate.
[0050] The preparation process of this invention is fully compatible with the existing tin-based perovskite solar cell preparation process. The preparation conditions are mild and the operation is simple. There is no need to make complex modifications to the existing production equipment. It has good repeatability. The introduction of SBF molecules only requires adding and stirring the precursor solution. It can effectively reduce the cost and threshold of large-scale production and is easy to achieve industrial mass production.
[0051] The tin-based perovskite solar cells prepared using the method of this invention achieve leading performance and stability among similar devices: the fill factor of small-area devices can reach 81.8%, the certified fill factor is as high as 84.13%, and the photoelectric conversion efficiency can reach 17.74% (certified efficiency 17.04%); 1 cm 2The large-area device has a photoelectric conversion efficiency of up to 15.11%, which has good potential for large-scale application. After packaging, the device can retain 89% of its initial efficiency after being stored under environmental conditions for 1100 hours and 86% of its initial efficiency after being continuously irradiated with 1-sun light for 1000 hours. Its long-term stability is significantly better than that of existing unoptimized devices, and it has good prospects for practical application.
[0052] In some preferred embodiments, the method for fabricating the tin-based perovskite solar cell specifically includes the following steps: (1) A PEDOT:PSS hole transport layer precursor solution is spin-coated onto a clean transparent conductive substrate surface and then annealed to form a hole transport layer.
[0053] (2) Prepare a tin-based perovskite light-absorbing layer on the hole transport layer.
[0054] (3) An electron transport layer, a hole blocking layer and a metal electrode layer are sequentially prepared on the above perovskite light-absorbing layer to obtain the tin-based perovskite solar cell based on the synergistic regulation of bulk phase and interfacial carrier dynamics by SBF molecules.
[0055] Preferably, the hole transport layer precursor solution is a PEDOT:PSS aqueous dispersion; the spin coating speed is 4000~6000 rpm, for example, 4000 rpm, 5000 rpm, 6000 rpm, etc., more preferably 5000 rpm; the spin coating time is 30~40 s, for example, 30 s, 35 s, 40 s, etc., more preferably 30 s; the annealing temperature is 120~140℃, for example, 120℃, 130℃, 140℃, etc., more preferably 140℃; the annealing time is 15~20 min, for example, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, etc., more preferably 15 min. After annealing, a uniform and dense hole transport layer is formed, laying the foundation for subsequent carrier extraction and providing support for the enrichment of SBF molecules at the buried interface.
[0056] Preferably, the electron transport layer is prepared by spin-coating an electron transport layer precursor solution onto the surface of the tin-based perovskite light-absorbing layer and then annealing it; the electron transport layer precursor solution includes indene-C60 bisadduct (ICBA); the spin-coating speed is 2000 rpm and the spin-coating time is 30 s; the annealing temperature is 70℃ and the time is 10 min.
[0057] Preferably, the hole blocking layer is prepared by spin-coating a hole blocking layer precursor solution onto the surface of the electron transport layer and then annealing it; the hole blocking layer precursor solution contains 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP); the spin-coating speed is 6000 rpm and the spin-coating time is 30 s; the annealing temperature is 70°C and the time is 10 min.
[0058] The electron transport layer and hole blocking layer work together to improve electron extraction efficiency and suppress interfacial nonradiative recombination, forming a synergistic effect with the interfacial regulation of SBF molecules.
[0059] The present invention will now be described in detail with reference to specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0060] In the following embodiments, unless otherwise specified, all raw materials used are commercially available conventional raw materials, all processing technologies used are conventional processing technologies in the relevant technical field, all equipment used are conventional laboratory equipment, and all operating conditions are conventional operating conditions, which can be appropriately adjusted according to actual conditions.
[0061] It should be noted that Spiro-OMeTAD mentioned in the following examples is 2,2,7,7-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorene (SBF), which are different expressions of the same substance; the tin-based perovskite solar cells prepared in each example all have the same device structure of ITO / PEDOT:PSS / tin-based perovskite / ICBA / BCP / Ag, with only differences in the process parameters during preparation.
[0062] Example 1 This embodiment provides a tin-based perovskite solar cell, the fabrication process of which is as follows: (1) ITO substrate pretreatment and hole transport layer preparation: The etched ITO conductive glass substrate (100 nm) was ultrasonically cleaned for 15 min each with deionized water and anhydrous ethanol to remove surface oil and impurities. After cleaning, it was dried and then subjected to UV ozone treatment for 15 min to improve the hydrophilicity and cleanliness of the substrate surface. The filtered PEDOT:PSS aqueous dispersion was spin-coated onto the pretreated ITO substrate surface at a speed of 5000 r / min for 30 s. After spin-coating, it was annealed at 140℃ for 15 min. After cooling, a uniform and dense PEDOT:PSS hole transport layer with a thickness of 30 nm was formed.
[0063] (2) Preparation of tin-based perovskite light-absorbing layer: In a nitrogen glove box with an oxygen content of less than 0.1 ppm, phenylethyl ammonium bromide (PEABr), formamidinium hydrobromide (FABr), methylamine hydrobromide (MABr), stannous iodide (SnI2) and stannous fluoride (SnF2) were dissolved in a mixed solvent of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) with a volume ratio of 1:4. At the same time, SBF (Spiro-OMeTAD) was added and stirred until completely dissolved, so that the concentration of SBF (Spiro-OMeTAD) was 1 mg / mL, and a 1.2 M tin-based perovskite precursor solution was prepared. The precursor solution was coated onto the surface of the hole transport layer using a one-step spin coating method. The spin coating parameters were: 2000 rpm / s acceleration and 5000 r / min rotation speed for 50 s. At the 15th s of spin coating, 340 μL of the anti-solvent chlorobenzene was dropped onto the substrate surface to assist perovskite crystallization. After spin coating, the substrate was annealed at 80℃ for 10 min. After cooling, a dense, pinhole-free, and highly crystalline tin-based perovskite light-absorbing layer with a thickness of 450 nm was formed. At this time, SBF (Spiro-OMeTAD) molecules were uniformly distributed in the perovskite bulk phase, top, and buried interface, and were enriched at the buried interface.
[0064] (3) Preparation of electron transport layer and metal electrode layer: On the surface of the above-mentioned tin-based perovskite light-absorbing layer, an ICBA chlorobenzene solution with a concentration of 18 mg / mL was spin-coated at a speed of 2000 r / min for 30 s. After spin-coating, the layer was annealed at 70℃ for 10 min and cooled to form an ICBA electron transport layer with a thickness of 20 nm. Subsequently, a BCP isopropanol saturated solution was spin-coated at a speed of 6000 r / min for 30 s to form a BCP hole-blocking layer with a thickness of 8 nm. Finally, a silver electrode with a thickness of 90 nm was deposited by vacuum thermal evaporation, and a complete tin-based perovskite solar cell was obtained after deposition.
[0065] Example 2 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 0.5 mg / mL.
[0066] Example 3 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 1.5 mg / mL.
[0067] Example 4 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 2 mg / mL.
[0068] Example 5 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 3 mg / mL.
[0069] Example 6 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 0.2 mg / mL.
[0070] Example 7 This embodiment provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that the concentration of SBF is 3.5 mg / mL.
[0071] Comparative Example 1 This comparative example provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that: in step (2), SBF is not added.
[0072] Comparative Example 2 This comparative example provides a tin-based perovskite solar cell, the preparation process of which differs from that of Example 1 in that: in step (2), SBF is not added, but 2-(2-aminoethyl)–2-thiopseudourea dihydrobromide (AET) is used instead, with an AET concentration of 0.5 mg / mL.
[0073] Test case Test method: AM 1.5G, 100 mW cm -2 A standard solar simulator, in conjunction with a digital source meter, was used to test the photoelectric conversion efficiency of tin-based perovskite solar cells. Before testing, the light source intensity was calibrated using a standard silicon cell. The device electrodes were connected to the testing equipment via low-resistance probes. After being placed in the dark to eliminate light hysteresis, continuous voltage scanning was performed, and current-voltage (JV) curves were acquired. Open-circuit voltage, short-circuit current density, and fill factor were extracted, and the photoelectric conversion efficiency was calculated. Multiple devices were tested in parallel for each sample group, and the average and optimal performance values were used for performance comparison and analysis.
[0074] The test results are shown in Table 1. The test area is 0.04 cm². 2 .
[0075]
[0076] As shown in Table 1, the JV curves corresponding to different SBF doping concentrations in the examples reveal that when the SBF doping concentration increases from 0.2 mg / mL to 1.0 mg / mL, the fill factor and photoelectric conversion efficiency of the tin-based perovskite solar cell (TPSC) increase simultaneously, with 1.0 mg / mL being the optimal doping concentration, corresponding to a PCE of 17.74%. When the SBF doping concentration exceeds 1.0 mg / mL, the short-circuit current density, fill factor, and photoelectric conversion efficiency all show a gradual decline trend with further increases in doping concentration. When the SBF doping concentration increases to 2.5 and 3.0 mg / mL, the device performance further deteriorates. These results indicate that excessively high concentrations of SBF molecules introduce additional thin-film defects, hinder charge transport, and are detrimental to improving the photovoltaic performance of the device. In contrast, Comparative Example 1, which did not introduce SBF, showed significantly lower device performance, indicating that the single tin-based perovskite system suffers from intrinsic crystallization runaway and interface instability, lacking effective control methods. Although Comparative Example 2 introduced other additives, it failed to achieve synergistic optimization of the bulk phase and interface, suggesting that the function of SBF molecules cannot be simply replaced by conventional passivation molecules.
[0077] Depend on Figure 2 As can be seen, this invention employs steady-state photoluminescence (PL) detection technology to systematically investigate the regulatory effect of SBF molecular doping modification on the carrier dynamics of tin-based perovskite layers across the entire region (covering the perovskite bulk phase, top interface, and embedded interface). The sample systems used in this test comprise three types, with specific structures corresponding to the appendix. Figure 2The images show: 1) undoped tin-based perovskite films and SBF-doped tin-based perovskite films; 2) stacked structures constructed by combining undoped tin-based perovskite and SBF-modified tin-based perovskite with PEDOT:PSS hole transport layers (HTLs); and 3) stacked structures constructed by combining undoped tin-based perovskite and SBF-modified tin-based perovskite with ICBA electron transport layers (ETLs). Test results show that the power spectral density (PL) of the SBF-doped tin-based perovskite films is significantly improved compared to the undoped films, demonstrating that SBF doping can effectively reduce the defect state density of perovskite films, suppress nonradiative recombination behavior of charge carriers, and optimize the charge transport capacity within the bulk phase of the tin-based perovskite film. In contrast, in the stacked structures containing PEDOT:PSS hole transport layers and ICBA electron transport layers respectively, the SBF-modified stacked structures exhibited significant PL quenching compared to the corresponding original unmodified stacked structures, corresponding to a significant improvement in hole extraction efficiency and electron extraction efficiency, respectively. In summary, these steady-state PL test results effectively demonstrate that SBF molecular doping modification can simultaneously optimize the charge transport performance of the tin-based perovskite phase and improve the carrier extraction rate at the top and embedded interfaces of the perovskite, comprehensively improving the overall carrier dynamics of the tin-based perovskite layer. Further detailed test analysis results will further verify and confirm the effectiveness of this technology.
[0078] Depend on Figure 3 It can be seen that the methoxy group in the SBF molecule exhibits a strong electron-rich region (a) and the binding energy between the SBF molecule and SnI2 is -0.95 electron volts, which confirms that there is a strong interaction between the two (b).
[0079] like Figure 4 The characterization results show that after doping SBF molecules into the tin-based perovskite system, the average grain size of the perovskite film increased from the original 350 nm to 500 nm. Simultaneously, the morphological contrast between grains and grain boundaries in the SBF-doped tin-based perovskite film was significantly improved. These results confirm that SBF molecules can act as a molecular binder, effectively bonding adjacent perovskite grains. This optimizes the charge transport pathways within the film and improves charge transport efficiency, while also effectively suppressing nonradiative recombination of charge carriers in the grain boundary region, reducing film defect losses. The microstructure of the film was characterized using cross-sectional scanning electron microscopy, and the relevant results are as follows: Figure 4As shown in ef. Characterization results further demonstrate that the tin-based perovskite layer modified with SBF molecules can form a uniform, smooth, dense, and tightly packed thin film morphology. This optimized microstructure can effectively block direct contact between non-adjacent functional layers of the device, block potential leakage current conduction paths inside the device, and significantly reduce parasitic charge recombination centers in the thin film system, thereby improving the overall performance and operational stability of the tin-based perovskite device from the microstructure level; cross-sectional scanning electron microscopy images show that the TPSCs in Comparative Example 1 (e) and Example 1 (f) indicate that the SBF-treated tin-based perovskite layer forms a uniform, smooth, and dense layer.
[0080] Depend on Figure 5 As can be seen, the XRD patterns of the tin-based perovskite films of Comparative Example 1 (untreated) and Example 1 (SBF treated) (a) show that the crystallinity is improved after the incorporation of SBF molecules; FWHM of the (100) crystal plane images of the untreated and SBF-treated TPSCs (b); PL mapping of the untreated and SBF-treated tin-based perovskite films (c) and (d) shows that the crystallinity is enhanced after the incorporation of SBF molecules, confirming that the defect density is significantly reduced after the incorporation of SBF molecules; SCLC curves of the untreated and SBF-treated tin-based perovskite films (e) and TRPL curves of the untreated and SBF-treated tin-based perovskite films (f) show that the charge transport efficiency is high and the non-radiative loss is reduced in the bulk tin-based perovskite.
[0081] Depend on Figure 6 The TPV decay time constants (τ) of untreated and SBF-treated tin-based perovskites are 0.308 μs and 0.769 μs, respectively. The TPC decay times (τ) of untreated and SBF-treated tin-based perovskites are 0.641 μs and 0.114 μs, respectively. These results confirm the enhanced charge transport and suppressed non-radiative recombination in the bulk phase of SBF-treated tin-based perovskites.
[0082] Depend on Figure 7 As can be seen from all the figures, SBF molecules can effectively suppress Sn on the top / buried surface of tin-based perovskite layers. 2+ Oxidation. (f) indicates that SBF molecules can effectively suppress Sn oxidation on the top / buried surface of tin-based perovskite layers. 2+ Oxidation.
[0083] Depend on Figure 8 It can be seen that the incorporation of SBF molecules induces a smaller hysteresis. From Figure 9 It can be seen that the optimal SBF concentration is approximately 1.0 mg / mL.
[0084] To verify the repeatability and performance stability of the device fabrication process, this invention selected 20 independently fabricated TPSC devices for batch performance testing. The test results are as follows: Figure 10 As shown in the figure, the test data indicates that the photoelectric conversion efficiency data of the TPSC device modified by SBF molecular doping is more concentrated and the distribution range is narrower, which fully demonstrates that the SBF modification scheme can significantly improve the uniformity of device performance and has excellent process repeatability and mass production adaptability.
[0085] Depend on Figure 11 As can be seen, to verify the practical application potential of the modification strategy of this invention, effective active areas of 1 cm² were prepared respectively. 2 The performance results of unmodified and SBF-modified large-area tin-based perovskite solar cells (TPSCs) are as follows: Figure 11 As shown in figure a, the effective active area is 1 cm². 2 The difference between the preparation process of the unmodified TPSC and Comparison 1 lies in the area of the mask used during silver electrode deposition, which corresponds to different active areas. The effective active area is 1 cm². 2 The preparation process of the modified TPSC differs from that in Example 1 in that the mask area used for depositing the silver electrode is different, corresponding to different active areas. The unmodified large-area TPSC exhibits a power conversion efficiency (PCE) of 11.36%, an open-circuit voltage (VOC) of 0.749 V, a short-circuit current density (JSC) of 20.96 mA / cm², and a fill factor (FF) of 72.35%, performance comparable to existing similar devices. Compared to the unmodified device, SBF modification significantly improves the photovoltaic performance of large-area TPSCs. Testing showed that a 1 cm² SBF-modified TPSC achieves a PCE of 15.11%, a VOC of 0.987 V, a JSC of 21.37 mA / cm², and an FF of 71.63%.
[0086] Stability tests were conducted on unmodified and SBF-modified TPSCs after encapsulation at room temperature and atmospheric storage. The test results are as follows: Figure 11 As shown in b, the efficiency of the unmodified TPSC decays rapidly with storage time, retaining only 70% of the initial PCE after 1100 h; while the stability of the SBF-modified TPSC is significantly improved, maintaining 89% of the initial PCE under the same conditions. Simultaneously, the device's illumination stability was tested under continuous illumination conditions equivalent to 1 times the sunlight from a white LED. Figure 11c. After 1000 hours of continuous illumination, the PCE of the unmodified TPSC was only 62% of its initial value, showing significant performance degradation. The SBF-modified TPSC, after the same period of illumination, retained 86% of its initial PCE, effectively improving the device's stability under illumination. This stability improvement mechanism stems from the hydrophobic properties and rigid structure of SBF molecules: the hydrophobic properties effectively block moisture intrusion and inhibit moisture degradation of the perovskite film; the rigid molecular structure maintains the integrity of the perovskite lattice and inhibits structural damage, significantly optimizing the long-term service performance of the TPSC in terms of both environmental tolerance and structural stability.
[0087] Depend on Figure 12 As can be seen, the SBF-modified tin-based perovskite solar cell (TPSC) prepared in Example 1 of this invention has been independently and authoritatively tested and certified by the China Photovoltaic Industry Measurement and Testing Center (NPVM). The certified fill factor (FF) of the device can reach 84.13%, and the corresponding certified photoelectric conversion efficiency (PCE) is 17.04%, which is slightly lower than the FF of 81.8% and PCE of 17.74% measured by the applicant's laboratory (see Table 1), which is within the normal measurement deviation range.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tin-based perovskite light-absorbing layer, characterized in that, include: Tin-based perovskite crystal phase, and spirobisfluorene molecules doped in the tin-based perovskite crystal phase; The spirobifluorene molecules include 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene.
2. The tin-based perovskite light-absorbing layer according to claim 1, characterized in that, The spirobisfluorene molecules are doped on the surface and grain boundaries of the tin-based perovskite crystal phase.
3. The method for preparing the tin-based perovskite light-absorbing layer as described in claim 1 or 2, characterized in that, Includes the following steps: A tin-based perovskite precursor solution containing spirobisfluorene molecules is applied to the hole transport layer, followed by annealing to obtain the tin-based perovskite light-absorbing layer.
4. The method for preparing the tin-based perovskite light-absorbing layer according to claim 3, characterized in that, The mass concentration of the spirobifluorene molecules in the tin-based perovskite precursor solution is 0.5~3 mg / mL; Preferably, the concentration of the tin-based perovskite precursor solution is 0.9~1.4 M; Preferably, the components of the tin-based perovskite precursor solution include a tin source, an organic cation source, and additives; Preferably, the tin source includes one or both of stannous iodide and stannous fluoride; the organic cation source includes one or more of formamidinium hydrobromide, phenylethyl ammonium bromide, and methylamine hydrobromide; and the additive includes the spirobisfluorene molecule. Preferably, the molar ratio of the phenylethyl ammonium bromide, the formamidinium hydrobromide, the methylamine hydrobromide, the stannous iodide, and the stannous fluoride is 0.10~0.20:0.70~0.80:0.05~0.15:1:0.05~0.1; Preferably, the tin-based perovskite precursor solution further comprises a solvent; the solvent comprises one or both of dimethyl sulfoxide and N,N-dimethylformamide. Preferably, the volume ratio of the dimethyl sulfoxide to the N,N-dimethylformamide is 1:4~9.
5. The method for preparing the tin-based perovskite light-absorbing layer according to claim 3, characterized in that, The application method includes spin coating; Preferably, the spin coating rotation speed is 4000~8000 rpm, the acceleration is 500~2500 rpm / s, and the spin coating time is 30~60 s; Preferably, the antisolvent is added dropwise during the 10-20 s spin coating process; the antisolvent includes one or more of chlorobenzene, toluene, ethyl acetate, and isopropanol; the amount of antisolvent added is 250-400 μL. The annealing temperature is 70~90℃, and the annealing time is 8~15 min; Preferably, the annealing treatment is carried out in an inert atmosphere with an oxygen content of less than 0.1 ppm.
6. A tin-based perovskite solar cell, characterized in that, It includes a transparent conductive substrate, a hole transport layer, a tin-based perovskite light-absorbing layer as described in claim 1 or 2, or a tin-based perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode, which are stacked sequentially from bottom to top.
7. The tin-based perovskite solar cell according to claim 6, characterized in that, The transparent conductive substrate includes one or more of the following: indium tin oxide conductive glass, indium-free metal oxide transparent conductive oxide film, metal-based transparent conductive network, carbon-based transparent electrode, and conductive polymer film; Preferably, the hole transport layer includes a PEDOT:PSS hole transport layer; Preferably, the electron transport layer comprises an indene-C60 bisadduct layer; Preferably, the hole-blocking layer comprises a 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline layer; Preferably, the metal electrode is a silver electrode with a thickness of 80~100 nm.
8. The method for preparing a tin-based perovskite solar cell as described in claim 6 or 7, characterized in that, Includes the following steps: A hole transport layer, a tin-based perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode are sequentially stacked on a transparent conductive substrate.
9. The method for preparing a tin-based perovskite solar cell according to claim 8, characterized in that, The hole transport layer is prepared by spin-coating a hole transport layer precursor solution onto the transparent conductive substrate and then annealing it. Preferably, the hole transport layer precursor solution is a PEDOT:PSS aqueous dispersion; the spin coating speed is 4000~6000 rpm, the spin coating time is 30~40 s; the annealing temperature is 120~140℃, and the annealing time is 15~20 min.
10. The method for preparing a tin-based perovskite solar cell according to claim 8, characterized in that, The electron transport layer is prepared by spin-coating an electron transport layer precursor solution onto the surface of the tin-based perovskite light-absorbing layer and then annealing it; the electron transport layer precursor solution includes an indene-C60 bis-adduct; the spin-coating speed is 2000 rpm and the spin-coating time is 30 s; the annealing temperature is 70℃ and the time is 10 min. Preferably, the hole blocking layer is prepared by spin-coating a hole blocking layer precursor solution onto the surface of the electron transport layer and then annealing it; the hole blocking layer precursor solution contains 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline; the spin-coating speed is 6000 rpm and the spin-coating time is 30 s; the annealing temperature is 70℃ and the time is 10 min.
